BUDAYA ORANG BASUDARA DALAM PERSFEKTIF AL-QURA’AN - M. Syafin Soulisa (Jurnal Studi Islam, 2020)
The article with the theme The Basudara Culture in the Perspective of the Al-Qur'an is an attempt to look at the problems of the Basudara culture in the eyes of the Qur'an. This paper is an attempt to see the culture of the Basudara (Maluku) people according to the view of the Qur'an. The discussion in this paper uses a literature review approach with the main source being the Qur'an and its books of interpretation, both classical and contemporary, using the thematic interpretation model (Maudhu'i). As a conclusion in this paper, it is found that the Qur'an has discussed culture which is characterized by all human activities as perfect creatures of Allah. With the various advantages that Allah has given to humans compared to other creatures, with all their potential, to determine a better way of life. The advantage is the creative potential (culture). The culture of the Basudara Gandong, Pela, Masohi and Sasi people. Gandong is a genealogical concept of family life of the Basudara people. In the perspective of the Qur'an, there are several sentences that focus more on family terminology, namely Al-'Alu, Al-Ahl, Asyirah, Rahm, Rukn, Al-Qurba. Al-Alu . Pela is mentioned in the Qur'an by using the phrase Ukhuwah which comes from the word "Akha-yakhuu" which means to be a brother or friend. Masohi in the study of the Koran is called Ta'awun, While Sasi, the Koran uses the terms Nahyu and al-Amar to indicate prohibitions and orders with a certain time limit.